Assessment of the Efficacy of Antiemetic Medications in Reducing Postoperative Nausea and Vomiting among Patients Undergoing General/Regional Anesthesia: A Descriptive Cross-Sectional Study in Albayda, Libya - Nusieba A Mohammed Ibrahim; Yahya Saber E Mansour (Libyan Journal of Medical and Applied Sciences, 2025)
Objective: Postoperative nausea and vomiting (PONV) is a common complication observed among most patients following surgical procedures performed under general or regional anesthesia. This study aimed to assess the incidence, severity, duration, and treatment of PONV in patients across a range of surgical procedures. Methods: A descriptive cross-sectional study was conducted among 150 patients admitted to Albayda Medical Center in Albayda, Libya. The participants were divided into two equal groups of 75 patients each—one receiving general anesthesia and the other receiving regional anesthesia. Results: Our findings revealed that the incidence of PONV was significantly higher among those in the general anesthetic group, with 50 out of 75 patients reporting PONV, in comparison to 30 out of 75 patients in the regional anesthetic group. The severity of PONV varied, with the general anesthetic group having 18 patients with mild nausea, 15 patients with moderate nausea, and 17 patients experiencing severe vomiting, and the regional anesthetic group recording 12 mild cases, 13 moderate cases, and 5 severe cases. The average duration of PONV symptoms ranged from 2 to 24 hours for the general anesthetic group, and from 2 to 6 hours for the regional anesthetic group. Antiemetic medications were given to 25 patients with PONV in the general anesthetic group and 10 patients in the regional anesthetic group. Among these participants, 15 in the general anesthetic group reported complete relief of PONV symptoms, while 10 reported partial relief. In contrast, 5 patients in the regional anesthetic group reported complete relief of symptoms while the remaining 5 reported partial relief. Conclusions: Our results indicate that general anesthesia is associated with a higher incidence and greater severity of PONV, as well as prolonged duration of symptoms compared to regional anesthesia. Therefore, it is essential to select suitable anesthesia techniques to reduce PONV symptoms and improve antiemetic treatment approaches to ensure timely and adequate relief of symptoms, particularly among patients undergoing general anesthesia.